PLAGIARISM DETECTION PROBLEMS AND ANALYSIS SOFTWARE TOOLS FOR ITS SOLVE - Shynkarenko, V. I.; Kuropiatnyk, O. S. (Science and Transport Progress, 2017)
Purpose. This study is aimed at: 1) the definition of plagiarism in texts on formal and natural languages, building a taxonomy of plagiarism; 2) identify major problems of plagiarism detection when using automated tools to solve them; 3) Analysis and systematization of information obtained during the review, testing and analysis of existing detection systems. Methodology. To identify the requirements of the software to detect plagiarism apply methods of analysis of normative documentation (legislative base) and competitive tools. To check the requirements of the testing methods used and GUI interfaces review. Findings. The paper considers the concept of plagiarism issues of proliferation and classification. A review of existing systems to identify plagiarism: desktop applications, and online resources. Highlighting their functional characteristics, determine the format of the input and output data and constraints on them, customization features and access. Drill down system requirements is made. Originality. The authors proposed schemes complement the existing hierarchical taxonomy of plagiarism. Analysis of existing systems is done in terms of functionality and possibilities for use of large amounts of data. Practical value. The practical significance is determined by the breadth of the problem of plagiarism in various fields. In Ukraine, develops the legal framework for the fight against plagiarism, which requires the active solution development tasks, improvement and delivery of relevant software (PO). This work contributes to the solution of these problems. Review of existing programs, Anti-plagiarism, as well as study and research experience in the field and update the concept of plagiarism, the strategy allows it to identify more fully articulate to the functional performance requirements, the input and output of the developed software, as well as to identify the features of such software. The article focuses on the features of solving the problem of identification of borrowing in an academicenvironment.